Experimental study of single- and two-phase heat transfer of fractal-like structures - Phua, Shi Yang (Nanyang Technological University, 2021)
When looking at the advancement of technology nowadays, the need for a better heat-dissipating method is always being researched. One common way that is currently being used in personal computers around the world is the use of liquid cooling systems. However, just using liquid without utilising the change of state to absorb heat or the flow of the liquid is a slight waste of existing resources. In this project, the focus will be looking at the utilisation of the change of state from liquid to vapour to put the latent heat of vaporisation into use, as well as to look into whether fractal-like structures are viable for the use of drawing heat away from heat-generating devices. Four fractal-like structures, with varying bifurcation angles (25°, 30°, 35°, 40°) were fabricated with the use of Selective Laser Melting (SLM) technology, with four levels of branching. The channels within these fractal-like structures are semi-circular in cross-section, with a diameter ratio of 2-1/3 and a length ratio of 0.5. A four-channel horizontal, semi-circular cross-section, parallel flowing structure is used as a comparison against the fabricated fractal-like structures. The use of 400kg/m2·s and 800kg/m2·s mass fluxes will be the basis of the flow rate within the system in this experiment, and FC-72 is the coolant that is used. It was observed that the fractal-like structure with a bifurcation angle of 25° had the lowest values of heat transfer coefficients, subsequently followed by the fractal-like structures of 30°, 35° then 40° for single-phase heat transfer. The heat transfer performance improvements were different for each fractal-like structure and were not linear to the increments of the bifurcation angles. There was no solid conclusion made to the comparison of the heat transfer performances between the parallel structure and the fractal-like structure at θ = 30°. Pressure drop values were on average 7% higher for every increment of 5° on the bifurcation angle for single-phase heat transfer. This, however, has no relation to the amount of improvement to the heat transfer performance of the fractal-like structures. Improvements in the heat transfer performance were not proportionate to the increase of pressure drops. The increase in mass flux led to heat transfer performance as well as an to the increase in pressure drop curves. However, the experiment was only done on one fractal-like structure and would need more experiments to confirm the fact.